Analisys of territorial aspects and results of major development programs in Vojvodina - Juhász, Bálint; Pleschinger, Gyula (Studia Mundi – Economica, 2021)
Vojvodina is currently one of the country's leading regions in economic terms, due to its good geographical position, centuries-old traditions, processing industry which depends on a high[1]quality arable land and the backwardness of other regions. The territorial and economic development of Vojvodina as a region is based on a similar extent on exogenous ad endogenous forms of development. The two most important instruments of exogenous development are the European Union's Instrument for Pre-Accession Assistance (IPA) and the Vojvodina Economic Development Program, prepared and fought by the Alliance of Vojvodina Hungarians, and with the support of the Hungarian Government. The research covers the territorial distribution of development resources, the absorption capacity of each local government area, the level of support per capita, and examines the correlations arising from the contexts and peculiarities of the two programs.